Karakteristik Kewirausahaan Masyarakat Pemulung Pendekatan Fenomenologi terhadap Komunitas Pemulung di Tempat Pembuangan Akhir Sampah Bantar Gebang Kota Bekasi - Soimah (Jurnal Aplikasi Manajemen, 2013)
The objective of this study is to determine the characteristics of the entrepreneurialscavengers society: scavengers (pemulung), pelapak and bandar. The research location is at Bantar Gebang Bekasi waste disposal. The Research used phenomenology qualitative approach. The sampling method is purposive sampling, namely by choosing a sample from the scavengers society members who have had experience of at least 5 years. The data was collected by in-depth interviews and direct observation inthe field. Data analysis was conducted qualitatively by exposing the phenomenological meanings implied in the experience of the interviewees. The results of this study find that entrepreneurial characteristics are different for each member of the scavenger community. Characteristics of scavengers are: self-confident, patient and persistent, internal motivation, work in earnest, and hard work; meanwhile the pelapak andbandar have similar entrepreneurial characteristics like what the scavengers have and five other characteristics namely: the courage to take risks, good at communication, intelligent reading opportunities, future orientation, and leadership.